Evaluation of Candidates Performance in Core Subjects and Financial Accounting in the May/June 2014 Wassce in Egor and Oredo Local Government Areas, Edo State, Nigeria - Udom, Idongesit David (LPPM Universitas Malikussaleh, 2024)
This study is designed to carry out an Evacuation of Candidates Performance in Core Subjects and Financial Accounting in the May/June 2014 WASSCE in Egor and Oredo Local Government Areas, Edo State, Nigeria. To be able to evaluate performance, the researcher raised five research questions, four of which were hypothesized. The statement of problem included the perceived attitude of trying to shift blames for failures in school examination to teachers. A comprehensive and empirical review of both related literatures and studies on West Africa Senior School Certificate Examination results were also done to enable the researcher paint a picture of what has been obtainable prior before now on performances of students especially in Financial Accounting. A Proforma titled Core Subjects and Financial Accounting in the May/June 2014 WASSCE in Egor and Oredo Local Government Areas Edo State, Nigeria,was used to collect data from the sampled secondary schools the public senior secondary schools in Egor and Oredo Local Government Areas. Data analysis was done by an expert in measurement and evaluation using descriptive statistics, ANOVA, t-test of independent sample etc.The findings of the study revealed that candidates performed relatively well in both the Core Subjects (including Financial Accounting) in the May/June 2014 WASSCE. The findings also revealed that the teachers were effective and efficient in carrying out their duties. Based on the findings, recommendations were made for improvement in future.